2022
DOI: 10.14704/web/v19i1/web19224
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Integrate E-Medical System Using Software Defined Networking and Machine Learning

Abstract: Scholars and medical professionals have recognizes the importance of electronic medical monitoring services for tracking elderly people's health. These platforms generate a large amount of data, requiring privacy and data security. on the contrary, Using Software Defined Networking (SDN) to maintain network efficiency and flexibility, which is especially important in the case of healthcare observation, could be a viable solution. Moreover, machine learning can additionally utilized as a game changing tool whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To improve the security and stability of network communication, machine learning technology and SDN network were combined to ensure system security and stability, display and extract network characteristic data, and identify and screen risk data. The proposed model had good feasibility after comparing several risk detection models [11].…”
Section: Related Workmentioning
confidence: 93%
See 2 more Smart Citations
“…To improve the security and stability of network communication, machine learning technology and SDN network were combined to ensure system security and stability, display and extract network characteristic data, and identify and screen risk data. The proposed model had good feasibility after comparing several risk detection models [11].…”
Section: Related Workmentioning
confidence: 93%
“…In equation (11), i p represents the probability of the protocol type. In the SDN framework, the characteristic data of DDoS attacks can also be extracted by analyzing the flow.…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…Pankaj et al [21] used a machine learning approach to diagnose diabetes using the M-Health application. Abed et al [22] introduced an integrated electronic medical system that enables efficient medical monitoring. Here, the machine learning based traffic flow classification model was utilized for reducing the time delay and traffic during data transmission/communication.…”
Section: Related Workmentioning
confidence: 99%
“…[15] have indicated that emerging technology and advanced information technologies have opened new doors to innovation nding and enhancement for everlasting solutions to producing effective and resolute healthcare provision in our daily lives [15]. The spring in predictive systems has also been faced with challenges in the developmental stages which require improvement since the issues regarding Covid-19 are numerous and lack clear "standard operating procedures," in addressing it medically [16], [17]. This according [18] requires a potential to automate systems' tasks and improve in existing systems to be able to improve healthcare provision and patient care in general [19].…”
Section: Introductionmentioning
confidence: 99%